2014
DOI: 10.5455/2349-3291.ijcp20140804
|View full text |Cite
|
Sign up to set email alerts
|

A study on relevance of mid arm circumference measurement among 13-60 months of children at urban field practice area of Alluri Sita Ramaraju Academy of Medical Sciences, Eluru

Abstract: Background: Protein energy malnutrition commonly seen in 2 to 5 years of age group in developing countries like in India. This could be due to lack of awareness about nutritive value of foods, faulty feeding practices, ignorance plays a major role in the development of Protein malnutrition in early ages of life. This leads to hampering of physical and mental development of the child. Objectives of current study were: 1) To know the prevalence of protein energy malnutrition among 13-60 months of children. 2) To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moreover, MUAC is a better predictor of death than WHZ 12. A study from India documented that measurement of MUAC was found to correspond with WHZ in mild to moderate malnutrition (87.5%) but in severe malnutrition it was low (70%) 13. When single MUAC cut-off (< 12.5 cm), and WHZ < -2SD were compared in a study done by Mogendi there was no statistically significant difference in sensitivity and specificity 14.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, MUAC is a better predictor of death than WHZ 12. A study from India documented that measurement of MUAC was found to correspond with WHZ in mild to moderate malnutrition (87.5%) but in severe malnutrition it was low (70%) 13. When single MUAC cut-off (< 12.5 cm), and WHZ < -2SD were compared in a study done by Mogendi there was no statistically significant difference in sensitivity and specificity 14.…”
Section: Discussionmentioning
confidence: 95%
“…The results were similar to the study conducted by Choudhary et al from Eluru A. P. India where mild to moderate malnutrition was found in 24% but severe malnutrition was 7.5% in their study. 29 Higher prevalence of malnutrition from India was reported by Verma et al (48.7%), Avachat et al (50.46%) and Bant et al (49.1%). 16,23,31…”
Section: Discussionmentioning
confidence: 78%